Impact of the single euro payment area on performance of banking sector - Todorović, Violeta; Sedlarević, Lazar; Tomić, Nenad (Industrija, 2017)
The European banking sector has gone through significant changes during the past decade. In addition to changes in the regulatory framework, it is important to emphasize establishment of a single payment area in the Euro-region (SEPA) whose primary objective was improvement of efficiency to all business entities. As the banks are one of the participants in the implementation process, the main objective of this study is to determine the effects of the implementation of SEPA rules on performance of banking sectors in the EMU. The paper presents a methodological framework and work on models to measure the impact of implementation SEPA rules on the performance of the banking sector. The model is based on regression in which SEPA payment instruments are used as independent variables. Data relates to banking sectors of 17 countries, members of EMU and cover the period 2002-2012. Each of the 17 members of the EMU is classified into one of the three groups, with as criteria of classification used indicator of the average participation of banking sector assets of a particular state in average assets of the banking sector EMU. Results of the research are in cohesion with the views that in the short term benefits of SEPA project is not enough in compare with the costs.